Smart health-care systems for rheumatology - Suneeta Mohanty; Prasant Kumar Pattnaik (Indian Journal of Rheumatology)
Smart health care comprises e-health, m-health, electronic resource management, smart and intelligent home services, and medical devices. Wireless sensors, radio-frequency identification technology, Internet of things, and machine learning (ML) algorithms are the underlying technology to implement smart health care. Sensor plays a vital role in smart health care for the collection of real-time data. Sensors such as accelerometers, wearable sensors, and thermal infrared camera sensors are extensively used to assemble data for patients with arthritis. ML algorithms are used to observe ailments and classify patients with respect to various diseases. This article presents a basic introduction to these concepts, existing smart health-care applications for rheumatology along with the pros and cons of smart health-care system. This article will help the researchers working in the field of medicine to understand the underlying technology of smart health-care systems.